1996
DOI: 10.1530/eje.0.1350489
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific changes in thyroid hormone-glucuronidating enzymes in rat liver during short-term fasting and long-term food restriction

Abstract: Glucuronidation is a major pathway of thyroid hormone metabolism in rats, involving at least three different hepatic UDP-glucuronyltransferases (UGTs): bilirubin UGT, phenol UGT and androsterone UGT. We have studied the effects of short-term (3 days) fasting and long-term (3 weeks) food restriction to one-third of normal intake (FR33) on hepatic UGT activities for thyroxine (T4), triiodothyronine (T3), bilirubin and androsterone in male and female Wistar rats with either a functional (high activity, HA) or a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…experiment I, seems to be in agreement with findings of van Haasteren et al (1996). These authors concluded that thyroid-stimulating hormone (TSH) release might be lowered by increased corticosterone secretion, although the mechanism of this effect may differ between acute starvation and prolonged food reduction in rats.…”
Section: Discussionsupporting
confidence: 89%
“…experiment I, seems to be in agreement with findings of van Haasteren et al (1996). These authors concluded that thyroid-stimulating hormone (TSH) release might be lowered by increased corticosterone secretion, although the mechanism of this effect may differ between acute starvation and prolonged food reduction in rats.…”
Section: Discussionsupporting
confidence: 89%
“…For example, mouse and human ABCC2 are known to be high affinity transporters for bilirubin-glucuronide and contribute to bilirubin excretion to bile (21). Fasting increases bilirubin glucuronidation (51) and Abcc2 induction could be in response to increase bilirubin clearance. Second, as ABCC2-4 contributes to bile acid efflux from hepatocytes, induction might aid in decreasing the increased bile acid load that occurs with fasting.…”
Section: Discussionmentioning
confidence: 99%
“…It has further been shown that some UGT isoforms (UGT1A9, UGT2B4) are PPAR␣ target genes (Barbier et al, 2003a,b). PPAR␣ is naturally activated during fasting, and Visser et al (1996) showed that food restriction resulted in increased bilirubin and thyroid hormone UGT activities in rats. These findings suggest that UGT catalyzing the glucuronidation of thyroid hormones may be transcriptionally upregulated by activation of PPAR␣.…”
Section: Discussionmentioning
confidence: 99%